Antiviral Effects of Microalgae - Aybike Türkmen; İhsan Akyurt (Turkish Journal of Agriculture: Food Science and Technology)
Microalgae, also called phytoplankton by biologists, are very small plant-like organisms with a diameter of 1-50 micrometers without roots, stem and leaves. Microalgae, which have hundreds of thousands of species in both fresh waters and seas, form the lowest link of the food chain in aquatic ecosystems. Most species contain chlorophyll, use sunlight as an energy source, and convert carbon dioxide into biomass (biomass). Because of their role in the photosynthesis process, microalgae produce most of the oxygen in the atmosphere. It has a very wide biodiversity and is reported to contain more than 200 thousand species. As a result of genetic analysis, a continuous increase in microalgae species is observed. More than 15 thousand new chemical compounds have been discovered from algae in recent years. It has been observed that most of the bio compounds obtained from microalgae have antiviral effects. However, although extensive research has been done on the antibacterial, antioxidant and antifungal effects of these bioactive compounds, there is limited research on their antiviral effects. In these limited number of studies on the antiviral effects of microagines, it has been reported that some biocompounds isolated from algae may be effective against viruses that are the cause of diseases such as “HIV, SARS and AIDS”. However, the number of researches on viruses that cause today's biggest pandemic, such as coronavirus, of different biocompounds isolated from microalgae, is very small. To date, no vaccine that can be effective against the COVID-19 virus or a drug that can inhibit the reproduction of the virus has not been found. It is thought that micro or macro algae may be one of the most promising natural resources in solving this global health problem. Because Spirulina, which is a microalgae, has antiviral, anticancer, antidiabetic, antibiotic, antioxidant, prebiotic, cardiovascular system protective and antiallergic effects and these positive effects are caused by bioactive compounds found in high content (Rosales-Mendoza et al., 2020a). In this review, especially the antiviral effects of microalgae were tried to be summarized and it was tried to be emphasized that algae could be promising natural resources in the development of new antiviral drugs by our country's scientists.